CBFs Function in Anthocyanin Biosynthesis by Interacting with MYB113 in Eggplant (Solanum melongena L.). (14th November 2019) - Zhou, Lu; He, Yongjun; Li, Jing; Liu, Yang; Chen, Huoying
Abstract: Eggplant is rich in anthocyanins. R2R3-MYB transcription factors play a key role in the anthocyanin pathway. Low temperature is vital abiotic stress that affects the anthocyanin biosynthesis in plants. CBFs (C-repeat binding factors) act as central regulators in cold response. In this study, we found that SmCBF1, SmCBF2 and SmCBF3, via their C-terminal, physically interacted with SmMYB113, a key regulator of anthocyanin biosynthesis in eggplant. SmCBF2 and SmCBF3 upregulated the expression of SmCHS and SmDFR via a SmMYB113-dependent pathway. In addition, the transient expression assays demonstrated that co-infiltrating SmCBFs and SmMYB113 significantly improved the contents of anthocyanin and the expression levels of anthocyanin structural genes in tobacco. When SmTT8, a bHLH partner of SmMYB113, coexpressed with SmCBFs and SmMYB113, the anthocyanin contents were significantly enhanced compared with SmCBFs and SmMYB113. Furthermore, overexpression of SmCBF2 and SmCBF3 could facilitate the anthocyanin accumulation under cold conditions in Arabidopsis. Taken together, these results shed light on the functions of SmCBFs and potential mechanisms of low-temperature-induced anthocyanin biosynthesis in eggplant.